WOMEN'S DEVIATION IN MORTALITY AND SENSUALITY IN D.H LAWRENCE'S LADY CHATTERLEY'S LOVERS (PART 1) - Herien Wahyuningtyas Djoko Ardhityawan (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This paper is the first part of two articles that report the study of women’s deviation in morality and sensuality in D.H. Lawrence’s Lady Chatterley’s Lovers. Two problems are discussed in this study: (1) the kinds of deviation of the women’s character in Lady Chatterley's Lovers by D. H. Lawrence, and (2) the reasons for the deviations in women’s role to happen. The method employed in this study is library research that attempts at tracing the sources of information which are relevant to the study. The theoretical framework of the studies are: literary theory of character, literary theory of morality and ethical framework, literary theory of sensuality, literary theory of conflict and literary theory of deviation. The result of the study shows some kinds of deviation on the female characters, including juvenile delinquency, cheating, adultery, marital and family maladjustment, role problem, discrimination against minority group, bootlicking, bullying, gossiping, and alcoholism. The reasons for the deviation to happen include the immature personality and conflict with the society due to their unreadiness with the massive revolution in England.